Analysis of the 7s Framework of McKinsey in the UKM X Yogyakarta - Didik Widiantoro; Yulia Herawaty; Irfani Rizal; Nur Fitriyana (Universitas Katolik Soegijapranata, 2020)
UKM is a place for a group of citizens to develop skills in the business sector. The problem that often occurs is the lack of a working system. There is a weak system that regulates work patterns, both in individuals and groups. Another thing that was discovered was the lack of the ultimate goal of the UKM group. So that at work the human resources are only reasonable to fill spare time. In this study, researchers used a qualitative approach by using interviews and observations as data collection methods. The subjects of this study were members of UKM X Yogyakarta. The assessment approach applied by researchers using McKinsey 7s at three levels of approach namely, organizations, groups and individuals. From the results of the study it was found that UKM X Yogyakarta still does not have clear objectives in running the business and there are also some members who lack good job communication skills. This makes UKM X less productive and unable to compete with other SMEs. Researchers provide goal setting training recommendations to all members of UKM X to be able to resolve the above problems.